Determination of Surface Water Quality for Irrigation in Dinajpur - Md. Motaharul Islam; Mst. Taslema Nasrin; Md. Mofizul Islam (Turkish Journal of Agriculture: Food Science and Technology, 2021)
A research was carried out to assess the suitability of surface water for irrigation purposes. For this reason, 56 samples of surface water were collected from each union of Dinajpur sadar upazilla, Dinajpur. The analysis was included pH, EC, TDS, Ca, Mg, S, P, Na, K, Cl- and HCO3- to evaluate the suitability of surface water for irrigation purposes. Almost all the water samples were within the recommended pH value for irrigation and a great impact on crop production. With respect to electrical conductivity (EC) samples were low to medium salinity. For total dissolved solids (TDS), all samples were considered as freshwater for irrigation. On the basis of Ca, Mg, S, P, Na, K, Cl- and HCO3- all samples could safely be used for irrigation and would not affect the soils.